2004
DOI: 10.1074/jbc.m402768200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerate Mutase-derived Polypeptide Inhibits Glycolytic Flux and Induces Cell Growth Arrest in Tumor Cell Lines

Abstract: The putative tumor metastasis suppressor protein Nm23-H1 is a nucleoside diphosphate kinase that exhibits a novel protein kinase activity when bound to glyceraldehyde-3-phosphate dehydrogenase (GAPDH). In this study we show that the glycolytic enzyme phosphoglycerate mutase B (PGM) becomes phosphorylated in the presence of the Nm23-H1⅐GAPDH complex in vitro. Mutation of His-10 in PGM abolishes the Nm23-H1⅐GAPDH complex-induced phosphorylation. Nm23-H1, GAPDH, and PGM are known to co-localize as shown by free f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 38 publications
3
46
0
1
Order By: Relevance
“…It has been reported that PGAM1 can also be activated by dCTP in the presence of NME1, a nucleoside diphosphate kinase (Engel et al, 2004). In our analysis we detected a regulation of NME1 at the protein expression level before PGAM1 appears to be modified.…”
Section: Discussionsupporting
confidence: 62%
“…It has been reported that PGAM1 can also be activated by dCTP in the presence of NME1, a nucleoside diphosphate kinase (Engel et al, 2004). In our analysis we detected a regulation of NME1 at the protein expression level before PGAM1 appears to be modified.…”
Section: Discussionsupporting
confidence: 62%
“…Either 3KQ, 3KR, or wild type PGAM was overexpressed in HEK293 cells cultured in pyruvate-free media, and the concentrations of glucose, lactate, and alanine were measured. Growth in pyruvate-free media simplifies measurements of glycolytic flux (34). Compared with cells expressing PGAM and the 3KR variant, cells expressing 3KQ exhibited stimulated glucose consumption and a corresponding increase in lactate levels (Fig.…”
Section: And E)mentioning
confidence: 99%
“…Important for glycolytic flux in cells is phosphoglycerate mutase (21), which may play a similar role within trichomonads. Finally, there are numerous carbohydratedegrading and/or -modifying enzymes, some of which are highly expressed in the FN-EST transcriptome, and these enzymes may play an important role in aborting any lectin-type interactions between the parasite and the host cell.…”
Section: Fig 3 2-de Maps Of Trophozoites and Fn-bound Amoeboid Cells mentioning
confidence: 99%